Implementation of Standardization Policy for Cross-Border Service Posts - Rares, Joyce Jacinta (Borong Newinera Publisher, 2024)
Marore Island, which is part of the Sangihe Islands Regency, has for many years been a gateway and also a center for cross-border trade between the residents of the Sangihe Islands and the residents of the South Philippines. The strong inflow of goods then tends to be more